The effects of low-, medium-, and high-oil dried distillers grains with solubles (DDGS) on growth performance, nutrient digestibility, and fat quality in finishing pigs - Graham, Amanda Brooke (Kansas State University, 2013)
Three experiments used 1,756 pigs to evaluate the effects of corn dried distillers grains with solubles (DDGS) varying in oil content on growth performance, carcass characteristics, and fat quality in growing-finishing pigs. A fourth experiment used 12 pigs and determined the energy concentration and nutrient digestibility of the DDGS sources used in the previous 3 growth studies. Lastly, a fifth experiment used 576 pigs to determine the effects of DDGS and wheat middlings (midds) withdrawal 24 d before harvest in diets without or with ractopamine HCl (RAC) on growth performance, carcass characteristics, fat quality, and organ/intestine weights. Experiment 1 determined that increasing 7.4% oil DDGS decreased (linear, P < 0.02) ADG and G:F. Also, final BW, HCW, and carcass yield decreased (linear, P < 0.03), but jowl iodine value (IV) increased (linear, P < 0.001) as DDGS increased. Experiments 2 and 3 utilized DDGS sources that contained 5.2 vs. 9.3, and 9.2 vs. 11.8% oil, respectively. In brief, results suggested that while ADG was unaffected, feeding DDGS with 5.2% oil reduced G:F. In Exp. 4, stepwise regression was used to develop prediction equations based to determine that a 1% change in oil content of DDGS will change the DE by 71 kcal/kg and NE by 118 kcal/kg. Experiment 5 determined that pigs fed corn-soy (CS) diets throughout the finishing phase had greater (P < 0.03) ADG, G:F, and carcass yield and lower (P < 0.01) IV than those fed high fiber (HF; DDGS and wheat midds) diets throughout, with pigs fed the fiber withdrawal intermediately. Pigs fed RAC had greater (P < 0.01) ADG, G:F, and carcass yield than pigs not fed RAC. Iodine values were lowest (P < 0.01) for pigs fed the CS diets, highest (P < 0.01) for those fed HF diets throughout, and intermediate for pigs fed the withdrawal diet. Withdrawal of the HF diet to a CS diet partially mitigated negative effects on carcass yield and IV, and feeding RAC, regardless of dietary fiber regimen, improved growth performance and carcass yield.
Keywords: Corn; DDGS; Digestibility; Growth; Finishing pigs; Iodine value; Animal Sciences (0475)